2005
DOI: 10.1002/em.20155
|View full text |Cite
|
Sign up to set email alerts
|

Influence of DNA repair gene polymorphisms on the yield of chromosomal aberrations

Abstract: We evaluated the influence of several DNA repair gene polymorphisms on the frequency of chromosomal aberrations (CAs) analyzed in peripheral lymphocytes, using the fluorescence in situ hybridization technique. The CA data were obtained from an earlier study of 84 healthy nonsmokers (48 women and 36 men) carefully characterized for indoor radon exposure. The frequency of translocations showed a wide interindividual variability, which was only partly explained by age. To investigate the potential role of DNA rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 48 publications
5
23
1
1
Order By: Relevance
“…Individuals carrying XRCC3 Met241 have previously been shown to be deficient in DNA repair as attested by an increase in chromosome deletions using an in vitro cytogenetic challenge assay [Au et al, 2003] and by elevated levels of chromosomal translocations [Kiuru et al, 2005] and micronuclei [Angelini et al, 2005] following in vivo radiation exposures. However, although the present finding would appear to provide further support for an influence on DNA repair, the association between the XRCC3 Thr241Met SNP and G 2 radiosensitivity was not confirmed with FBAT analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals carrying XRCC3 Met241 have previously been shown to be deficient in DNA repair as attested by an increase in chromosome deletions using an in vitro cytogenetic challenge assay [Au et al, 2003] and by elevated levels of chromosomal translocations [Kiuru et al, 2005] and micronuclei [Angelini et al, 2005] following in vivo radiation exposures. However, although the present finding would appear to provide further support for an influence on DNA repair, the association between the XRCC3 Thr241Met SNP and G 2 radiosensitivity was not confirmed with FBAT analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphic variation in DNA repair genes has been reported to influence the response to in vitro irradiation as measured by cell cycle delay [Hu et al, 2001], cytogenetic damage [Lunn et al, 2000;Au et al, 2003;Marcon et al, 2003], and DNA single strand break induction and repair using the Comet assay [Aka et al, 2004;Godderis et al, 2004;Rzeszowska-Wolny et al, 2005]. However, whilst variation in DNA repair gene polymorphisms has been reported to influence the in vivo frequencies of micronuclei [Angelini et al, 2005] and unstable chromosome aberrations [Kiuru et al, 2005] following low dose irradiation, no such effect was found when stable translocations were used as the endpoint [Kiuru et al, 2005;Wilding et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in agreement with data from experimental models, where the XRCC3 241 T allele (Thr/Met amino-acid variation) was found to be associated with defective DNA repair. 48,49 Notably, SN-38 specifically targets Topo I and stabilizes the Topo I-DNA complex. Collision of this complex with moving DNA replication forks causes lethal double-strand DNA breakage and cell death.…”
Section: Folfiri Pharmacogenetics In Colorectal Cancermentioning
confidence: 99%
“…Some laboratory investigations of XRCC1 codon 399 Gln functionality in human cells suggested that this polymorphism is associated with increased levels of DNA damage after exposure to various mutagens (17)(18)(19). Other reports offered conflicting evidence, suggesting that the 399Gln polymorphism has no adverse effect on DNA repair (20)(21)(22). The 194Trp variant protein does not seem to negatively alter the DNA repair capacity of human cells (18,20).…”
Section: Introductionmentioning
confidence: 99%